Factors that influence the intention to adopt cryptocurrency as an electronic payment among young generation in Malaysia / Siti Najiah Kamaruddin - Kamaruddin, Siti Najiah (Faculty of Business and Management, 2019)
In recent years, a rapid growth has been seen in cryptocurrencies as a virtual currency throughout the world. Cryptocurrencies is a protocol which allows value to be exchanged over the internet without a central bank or intermediary. Cryptocurrencies are technological tools that arguably can contribute to reduced transaction costs. The usage of cryptocurrencies as electronic payment also has reached a significant number and continue to be increasing. The objective of this study is to analyze the factors that influence the intention to adopt cryptocurrencies as electronic payment among young generation. To carry out the goals, this study adapted TAM and UTAUT model and extended it by adding other variables which are awareness and perceived risk. A total of 64 respondents’ data were collected and analyzed by using Statistical Package for Social Science (SPSS) application. The findings of the study will give contributions to the government, financial institutions and industry players.